megaTALs: a rare-cleaving nuclease architecture for therapeutic genome engineering - Boissel, Sandrine (Oxford University Press, 2014)
Rare-cleaving endonucleases have emerged as important tools for making targeted genome modifications. While multiple platforms are now available to generate reagents for research applications, each existing platform has significant limitations in one or more of three key properties necessary for therapeutic application: efficiency of cleavage at the desired target site, specificity of cleavage (i.e. rate of cleavage at ‘off-target’ sites), and efficient/facile means for delivery to desired target cells. Here, we describe the development of a single-chain rare-cleaving nuclease architecture, which we designate ‘megaTAL’, in which the DNA binding region of a transcription activator-like (TAL) effector is used to ‘address’ a site-specific meganuclease adjacent to a single desired genomic target site. This architecture allows the generation of extremely active and hyper-specific compact nucleases that are compatible with all current viral and nonviral cell delivery methods.